Virtual screening, molecular docking, MD simulation studies, DFT calculations, ADMET, and drug likeness of Diaza-adamantane as potential MAPKERK inhibitors - Gheidari, Davood; Mehrdad, Morteza; Hoseini, Foroozan (Frontiers in Pharmacology, 2024)
Multiple sclerosis (MS) is an autoimmune and inflammatory disease that destroys the protective coating of central nervous system (CNS) nerve fibers and affects over 2.8 million people worldwide. Despite several studies on new therapeutic targets and lead compounds, MS disease has limited treatment options. This condition may be caused by a complicated interaction of environmental and genetic variables. Studies showed that MS-associated microglial cells' increased MAPK ERK activity may cause CNS inflammation and oligodendrocyte damage. Thus, screening for lead compounds that inhibit MAPK ERK may protect brain cells and slow disease progression. The study aims to discover compounds that may inhibit MAPK ERK as a novel approach for protecting the nervous system in managing MS. The study includes in silico methods, such as virtual screening, molecular docking, Density-functional theory (DFT) investigations (using the B3LYP/6-31++G(d,p) basis set in a gas phase environment), drug likeness scores, and molecular dynamic (MD) simulations. During the docking process with the MAPK ERK protein, it was shown that the ligand L12 receptor had the best binding affinity, with a docking score of -6.18 kcal/mol. To investigate the stability of the binding, a 100 ns MD simulation was performed on the complex formed by the MAPK ERK protein and L12. The receptor-ligand combination exhibited significant stability throughout the duration of the MD simulation. Additionally, the pharmacokinetic and drug-likeness properties of these ligands suggest that they have the potential to be considered viable candidates for future development in MS management.